Experimental study of immunotropic properties of metabolites of Bacillus subtilis B-9909 strain, promising in the formulation of a new hepatoprotector - N. А. Zabokritskiy (Медицинская иммунология, 2023)
This brief report is devoted to the experimental study of the immunotropic activity of a new compound, a metabiotic, based on metabolites (biologically active substances, BAS) produced by the saprophytic and safe standardized strain of Bacillus subtilis B-9909. The aim of the study was to experimentally evaluate the immunotropic effect of metabolites produced by probiotic microorganisms of the genus Bacillus of the culture of probiotic microorganisms of the Bacillus subtilis B-9909 on laboratory animals when modeling their toxic lesion. Metabolites were isolated from the culture fluid of the bacterial culture Bacillus subtilis, strain RNCIM (Russian National Collection of Industrial Microorganisms) B-9909, during its deep cultivation in a medium consisting of hydrochloric acid hydrolysate of soy flour or pancreatic hydrolysate of casein. The study of humoral status indicators in experimental groups of animals in assessing the therapeutic efficacy of an experimental metabiotic sample, in relation to the group receiving the ursosan comparison drug, was carried out by determining such quantitative serum parameters as the titers of immunoglobulins M, G, A, E, the IFNa titer and the concentration of circulating immune complexes. Liver damage was studied by modeling acute toxic hepatitis in white rats. Thus, the studies conducted to study the humoral status of laboratory animals receiving metabolites produced by probiotic microorganisms of the genus Bacillus of the culture of probiotic microorganisms of the Bacillus subtilis B-9909 on laboratory animals when modeling toxic damage in them, give grounds to conclude that the test sample of BAS has a significant immunomodulatory effect, in comparison with ursosan. This circumstance allows us to recommend this compound as promising for the creation of a new hepatoprotector drug candidate with an immunotropic effect.